Caracterização nutricional e antinutricional de folhas de Abelmoschus esculentus (L.) Moench; atividade microbiológica da lectina presente na fração 30% - Caluête, Maria Emília Evaristo (2012)
The non-conventional vegetables s leafy such as seeds, stems, leaves and crumbs, can be inserted in food as an alternative source of nutrients. Among the alternatives, there is okra s leaves (Abelmoschus esculentus), vegetable belonging to the Malvaceae family, is widespread in tropical regions. However, the bioavailability of nutrients can be affected by antinutritional factors. In view of the above, this study aimed to determine the nutritional composition, antinutritional (lectin, tannin and saponin) detection of phenolic compounds, characterization of this lectin and biological activity of the protein from Abelmoschus esculentus s leaves. The analysis were made of composition and content of antinutritional (lectin, saponin and tannin) in fresh leaves, blanched, cooked and lyophilized, focusing on the effect of different treatments on these parameters. The lectin was determined by hemagglutination activity against rabbit erythrocytes and ABO human system, and subsequently confirmed by the presence of specific carbohydrate. Inactivation was tested by means of heat treatment, the pH shock, resistance to denaturing agent, reducing and enzymatically. The fraction 30% underwent testing for antifungal and antibacterial activity. Tannins was determined by the Folin-Denis reactive, while hemolytic test was performed to test the presence of saponin. The fresh leaves, blanched, cooked and lyophilized present predominantly carbohydrate, 11.54%, 12.42%, 4.99% and 36.97% respectively, crude fiber, 3.85%, 4.21%, 3.86% and 12.88% respectively, calcium, 382.50%, 357% 366.50% to 691% and magnesium, 232.50% 237.50% 138.50% and 438 respectively. It was detected the presence of lectin, specific activity was higher in leaves bleached (11.14 HU / mgP) and total inactivation by heat treatment (100°C for 30 minutes) at basic pH. It was detected the absence of saponin. Displays total phenolic content of 19.27 mg GAE / g. The 30% fraction showed no inhibitory effect on the growth of fungi and bacteria. It was concluded that the Abelmoschus esculentus s leaves is high in carbohydrates, fiber and minerals Ca, Mg and K, low calorie and absent saponins, besides having antioxidant components. The heat treatment was able to inactivate this lectin and lower tannin content to acceptable values.